Intensity-encoded polymer optical fiber accelerometer - Antunes, P. F. C.
In this paper, we report the development and experimental implementation of a low-cost, compact, intensity-encoded accelerometer based on polymer optical fibers (POF). The proposed accelerometer sensor element relies on the misalignment between two POFs, being the external acceleration encoded in the optical signal intensity. The accelerometer performance was optimized by simulation, resulting in a coupling efficiency and modulation index values of 0.38 and 1.78, respectively. The implemented device has a sensitivity of 33.5 +/- 0.1 mV/g and a resonant frequency of 51.44 +/- 0.1 Hz, obtained for a signal to noise ratio of 20 dB. This value for the resonant frequency is suitable for applications in several fields, such as structural health monitoring of civil engineering structures.